Principal components analysis of basketball performance indicators - Csataljay, G.; O'Donoghue, P.; Hugehs, M.; Dancs, H. (World Congress of Performance Analysis of Sport VIII, 2008)
Principal components analysis is a useful tool that can contribute to the process of identifying the most critical performance indicators to use in performance analysis. However, the current investigation has shown that inconsistencies can exist between the principal components extracted and the performance indicators selected based on those principal components. These inconsistencies between the analysis of performance indicators and principal components indicate that caution must be taken when using principal components analysis to identify the most critical performance indicators. The technique should be used in conjunction with other approaches including expert coach opinion.